Increasing flour whiteness index on Amorphophallus paeoniifolius (Dennst.) Nicolson flour production by sodium metabisulfite - Muhammad, Supriyanto; Syah, Ikrar Taruna; Xyzquolyna, Deyvie (Anjoro: International Journal of Agriculture and Business, 2021)
This research aims to increase flour whiteness index to foot elephant yam (Amorphophallus paeoniifolius) flour along the production process. The chemical agents used in this research were sodium metabisulfite (Na2S2O5) and ethanol. The corms were treated by soakeing in sodium metabisulfite 4% (w/v) for 3 hours, adding with ethanol 96% at a ratio of 1:2 and then blended with a speed of about 12,000 rpm for 5 minutes then filtered, and blanching into sodium metabisulfite 4% (w/v) for 3 minutes. The result showed that using Na2S2O5 4% (w/v) as a chemical agent on the initial production of Amorphophallus paeoniifolius flour was able to produce flour with the highest whiteness index. Therefore, this method will produce Amorphophallus paeoniifolius flour more applicable for the diversity of the food industry, especially noodles, biscuits, and bakery.